Reflections from the learning of preceptors in the Pedagogical Residency Program (Research, Society and Development, 2022)
This article presents research carried out with preceptors of the Pedagogical Residency Program (PRP), together with the Federal Farroupilha Institute - Campus São Borja - RS (IFFAR-SB). In this perspective, we seek to ascertain the influences of PRP on the continued formation of the participating preceptors, as well as to develop the importance of learning during the development of this program. This qualitative research was developed from a case study, which stopped in the analysis of a specific reality of the continued formation of the preceptors of the Pedagogical Residency - PRP - Campus São Borja. Regarding the analysis of the collected data, Bardin content analysis was used. As results, it was found that preceptors miss continuous training to fill the gap that exists in the context of working with their students with adapted plans, because the difficulty is how to proceed with each student according to their specific needs, they felt satisfaction in having had the opportunity to participate and build differentiated knowledge within the formative processes, emphasizing the variety of themes addressed and also emphasized that the program began to be part of its pedagogical practice, besides providing the same moments of reflection and action in the development of their lives as educators, in their teaching, making their classes more attractive and consequently with a relevant quality, so as to signify their practice.